The effect of immersion heat-polymerized PMMA denture base resin in sungkai leaf extract (peronema canescens jack) on surface roughness and impact strength: Experimental study - Belinda, Evelyn; Tamin, Haslinda Z (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: Denture disinfection is essential for maintaining hygiene when using dentures. In recent years, various natural denture cleansers have been developed, including sungkai leaf extract (Peronema canescens Jack). Sungkai leaves contain tannins and flavonoids with antifungal properties; however, they also contain phenolic derivatives that can influence the surface roughness and impact strength of polymethyl methacrylate (PMMA). This study aims to analyze the effects of immersing PMMA denture bases in 30%, 40%, and 50% sungkai leaf extract on surface roughness and impact strength. Methods: The design of this research is laboratory experimental. Surface roughness measurements and impact tests were conducted on 32 samples (65 x 10 x 2.5 mm). The samples were divided into four groups with sungkai leaf extract concentrations of 30%, 40%, 50%, and aquadest as a control group. The samples were immersed for 2 days 12 hours and 50 minutes to simulate the daily soaking duration of 10 minutes/day over 1 year. The samples were measured using surface roughness tester for surface roughness measurements and Charpy impact tester for impact tests. The data were analyzed using univariate tests, One-way ANOVA, and LSD (Least Significant Difference). Results: One-way ANOVA test results showed a significance value of p=0.0001 (p<0.05), indicating that immersion of PMMA denture base in sungkai leaf extract 30%, 40%, and 50% significantly affected surface roughness and impact strength. Conclusion: The immersion of heat-polymerized PMMA denture base resin in sungkai leaf extract (Peronema canescens Jack) resulted in increased surface roughness and decreased impact strength. However, the changes produced at 30% concentration were lower compared to concentrations of 40% and 50%. Therefore, sungkai leaf extract at 30% concentration may serve as a viable natural alternative to dental cleaning agents.KEY WORDS: denture cleansers, sungkai leaf extract, polymethyl methacrylate, surface roughness, impact strengthPengaruh perendaman basis gigi tiruan resin akrilik polimerisasi panas dalam ekstrak daun sungkai (Peronema canescens Jack) terhadap kekasaran permukaan dan kekuatan impakABSTRAKPendahuluan: Dalam pemakaian gigi tiruan, disinfeksi perlu diperhatikan dalam menjaga kebersihan gigi tiruan. Sekarang ini telah banyak dikembangkan bahan alami sebagai pembersih gigi tiruan, di antaranya yaitu ekstrak daun sungkai (Peronema canescens Jack). Daun sungkai memiliki kandungan senyawa tanin dan flavonoid yang mampu bekerja sebagai antijamur, namun tanin dan flavonoid juga termasuk turunan senyawa fenol yang dapat memengaruhi kekasaran permukaan dan kekuatan impak resin akrilik polimerisasi panas (RAPP). Tujuan dari penelitian ini adalah untuk menganalisis perbedaan efek perendaman basis gigi tiruan RAPP dalam ekstrak daun sungkai 30%, 40%, dan 50% terhadap kekasaran permukaan dan kekuatan impak. Metode: Rancangan penelitian ini adalah eksperimental laboratoris. Sampel pada penelitian ini berjumlah 32 sampel (65 x 10 x 2,5 mm), yang dibagi menjadi 4 kelompok terdiri dari kelompok yang direndam dengan ekstrak daun sungkai 30%, 40%, 50%, dan kelompok kontrol (aquadest) yang direndam selama 2 hari 12 jam 50 menit (simulasi perendaman 10 menit/hari dalam 1 tahun). Sampel diuji menggunakan surface roughness tester untuk kekasaran permukaan dan charpy impact tester untuk kekuatan impak. Hasil penelitian dianalisis menggunakan uji univarian, One-way ANOVA, dan LSD (Least Significant Difference). Hasil: Hasil uji One-way ANOVA diperoleh nilai signifikansi p=0,0001 (p<0,05) yang menunjukkan terdapat pengaruh perendaman basis gigi tiruan RAPP dalam ekstrak daun sungkai 30%, 40%, dan 50% terhadap kekasaran permukaan dan kekuatan impak. Simpulan: Terdapat perbedaan efek perendaman basis gigi tiruan resin akrilik polimerisasi panas dalam ekstrak daun sungkai (Peronema canescens Jack) berupa peningkatan kekasaran permukaan dan penurunan kekuatan impak yang dihasilkan pada konsentrasi 30% lebih kecil dibandingkan dengan konsentrasi 40% dan 50%, sehingga ekstrak daun sungkai dengan konsentrasi 30% dapat dijadikan sebagai alternatif bahan pembersih gigi tiruan yang alami.KATA KUNCI: Bahan pembersih gigi tiruan, ekstrak daun sungkai, resin akrilik polimerisasi panas, kekasaran permukaan, kekuatan impak